Concept map implementation strategies in teaching and learning: a case study of biology subject / Siti Salwa Salleh ... [et al.] - Salleh, Siti Salwa; Wan Ghani, Wan Aryati; Hamka Kamaroddin, Juliana; Baharuddin, Suzana (Universiti Teknologi MARA, Sabah, 2021)
Biology is a remarkably complex subject. It takes imagining, memorising and remembering facts, concepts, and processes. Students perceive Biology as a challenging and an unexciting subject. Apart from that, it is difficult to develop skills in visualisation and imagination while trying to grow the students' reason and judgment. A comprehensive method to facilitate memorisation is required to tackle this issue. One of the approaches is by implementing a concept map (CM) in multimedia courseware as the teaching module. CM represents knowledge and facts in a visual and graphical form. With a proper design and development, CM helps assist students in their learning process. This paper describes the design and development process of multimedia teaching and learning prototype that applies CM for teaching biology. The objectives of this research are to propose a CM approach as well as to evaluate its effectiveness from end users' point of view, particularly biology subjects taught in secondary school Form Five syllabus. A standard model in multimedia application development known as ADDIE is applied in this research. Two experiments were conducted to evaluate the prototype application in which effectiveness and usability parameters are being measured. The result demonstrates 86% of the respondents perceived the tools as relatively useful, and both the pre-test and post-test revealed steady improvement in learning abilities. Therefore, this prototype is developed to better aid the process of teaching and learning of Biology.